Analisa Manajemen Risiko Pada UMKM Rental Motor Menggunakan Framework ISO 31000 dan Matriks Risiko Manajemen: Studi Kasus Laju Rental - Alifa Raudhatul Nisa; Naila Dwi Ananti; Wafiyati Nur Amrina; Dewi Resti Agustiani; Alfiana, A, H Hendrawan (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study uses Laju Rental as an object operating in the field of motorcycle rental services. As a business that depends on movable assets, this MSME faces various potential risks, such as vehicle damage, late returns, loss of units, and operational and administrative risks. The research method uses a qualitative descriptive approach and the ISO 31000 Framework analysis method to identify risks, analyze risks, evaluate risks, and treat risks and Risk Management Matrices in risk assessment. The results of the study show that most risks are in the moderate to high category, especially the risk of vehicle misuse and damage due to tenant negligence. MSMEs have implemented several mitigation efforts, such as verifying renter identities, using rental agreements, and conducting regular maintenance, but risk management still needs to be improved through a more structured monitoring system and diversification of control strategies. This study is expected to provide insight for similar MSMEs in improving the effectiveness of risk management to maintain business sustainability.